Answer:
Explanation:
First find the slope of the given line.
y - 3 = 1/3(x+2)
y - 3 = (1/3)x + 2/3
y = (1/3)x + 2/3 + 3
y = (1/3)x + 11/3
Compare it with
y = mx + c
We get m = 1/3
As the parallel lines have same slope, the slope of the second line will also be m= 1/3
y = mx + c
y = (1/3)x + c
As this line goes through the point (1,7), substitute it in the equation:
7 = (1/3)1 + c
7 = 1/3 + c
c = 7 - 1/3
c = 21-1/3
c = 20/3
The equation of the line is found by substituting m = 1/3 and c = 20/3 into the general equation
y = mx + c
y = (1/3)x + 20/3
Graph of the equation is shown